Contested Waters: Political Ontologies of Water and the Production of Risk in First Nations Water Systems - Dokis, Carly; Restoule, Randy; Kelly, Benjamin (Anthropologica, 2025)
Indigenous communities in Canada are disproportionately affected by unsafe and insecure water systems. While inadequate federal funding and regulatory gaps have been identified as key barriers to the provision of safe drinking water on reserves, much less attention has been paid to the ways in which water quality risks are defined and managed by state actors, and the consequences of these rationalities and technologies of regulation for Indigenous peoples. Renewed ethnographic attention to infrastructure has called attention to the ways in which infrastructures are critical sites through which narratives, technological assemblages, ideologies, political rationalities, aesthetics, and sensory experiences are produced, encountered, and contested. Infrastructures and their administration are also deeply biopolitical projects that facilitate discipline and control. In this article, we show how water infrastructures are closely tied to ongoing colonial processes that serve to subjugate and, at times, blame Indigenous people for insecure water quality on reserves. In doing so, we interrogate the normative practices and techniques through which the Canadian state assesses water quality risks in Indigenous communities and the associated consequences for water governance.